Orthodontic treatment with clear aligner of a pre-rehabilitation trauma patient: case report - Alexandre Fausto da Veiga Jardim; Taina Itana Coelho Lima; Lucas Rodrigues Araújo Estrela; Carlos Estrela (Revista Sul-Brasileira de Odontologia, 2025)
To report a multidisciplinary case involving rehabilitation and orthodontics in a patient with a history of a car accident. Case report: A 22-year-old female patient, AQ, presented with a complaint of orthodontic correction and prosthetic rehabilitation of teeth lost in a car accident. The patient exhibited a Class III malocclusion with a right subdivision, mesialized lower segment, and crowding on this side. Teeth 11, 12, and 13 were missing and replaced by a removable prosthesis. Additionally, dental bimaxillary protrusion was observed. The proposed treatment included distalization of the lower right segment to correct crowding and distalization of the upper segments to improve dental inclination. The patient requested the use of clear aligners for orthodontic treatment. Distalization was performed using support from an extra-alveolar mini-implant in the right buccal shelf region. Proper sequencing of movements was crucial in the treatment planning. In the upper arch, dental implants with provisional crowns were placed in an ideal position to serve as a reference for final positioning and as anchorage for dental movement. At the end of the treatment, correction of dental crowding and improvement in dental inclination were achieved, enabling the patient’s rehabilitation. Conclusion: Proper planning integrating different specialties is essential to achieve an ideal clinical outcome. Dental implants provide absolute anchorage for orthodontic movement and, when combined with virtual planning, can be a valuable tool for case resolution without compromising patient esthetics.